Where did the Eco go in Systemic Practice? - Palmer, Hugh (Murmurations: Journal of Transformative Systemic Practice, 2021)
In this paper, I argue that, although the systemic therapy community adopted some of Gregory Bateson’s ideas, we neglected his ecological concerns, and his thinking about epistemology and ontology might have shaped our practice even more than the comparatively few concepts we took. With rising concerns about the impact of humans upon the environment in the era in which we live, described as the Anthropocene, along with the posthuman turn, perhaps now is the time for us to look both backwards and forwards to deepen our understanding of Bateson’s message; to acknowledge the continuing importance of his thinking and influence upon the posthumanities.